THE CONTRIBUTIONS ON THE STUDENT’S WAY OF LEARNING TOWARDS STUDY RESULT ON BUILDING MATERIALS TRAINING EDUCATION CLASS X, CONSTRUCTION ENGINEERING MAYOR AT PADANG VOCATIONAL HIGH SCHOOL 1 - 1947-1964 , Eldiansyah Putra (CIVED, 2016)
The problem in this research is the bad way of student’s way of learning, it proves by the unprepared condition of student’s in the building material lesson, and almost 40% of the student’s score is below the completeness standard criteria (CSC).  This  research  is  aimed  to  express  how  big  the  contributions  on  the student’s way of learning toward the study result on building materials training education class X, construction engineering mayor at Padang Vocational High School 1. The research hypothesisis that there is a contributionon The Student’s Way of  Learning  Towards  The  Study Result  on  Building  Materials  Training Education Class X, Construction Engineering Mayor At Padang Vocational High School 1. The population in this research is all of the students in construction engineering mayor that studied about construction materials training education that consist of 66 students. Sample taking technique is a total sampling with the sample amount 66 students.Data type that had been using is a primary and secondary data. Primary data was obtained by distributing the questionnaire about studying method to the students, while secondary data is a learning result in a form of scores of Construction Materials Lesson by the students. Analysis technique data that had been  used  are:  (1)  Descriptive  Analysis,  (2)  Analysis  condition  testing,  that consist of normality testing and linearity testing to prove that data distributions based  on  samples  that  distributed  normally  and  linearly,  and  (3)  hypotheses testing.Analysis result shows that the way of learning contributes 60.9% toward the study result of Class X Construction Engineering Mayor, Padang Vocational High School 1. This thing can be seen from score Sig (2-tailed) 0.000<Alpha (0.05). Based on that testing, it means that there is a positive connection between student’s way of learning Towards Study Result on  Building Materials Training Education Class X, Construction Engineering Mayor At Padang Vocational High School 1. Keywords: Contributions, Way of Learning, Learning Result